ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2009-2013) - Novita Sari, Dita; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2015)
Funding decisions a company to fund its operations, must be in accordance with the main objectives of the company. The funding decision was able to minimize the risks and costs that the company's main goal is reached. To achieve the goal, the company must have an optimal capital structure. The many factors affecting capital structure or debt policy, the study aims to analyze the factors that influence the policy of the company's debts. The independent variable of this study consisted of liquidity (CR), sales growth (SG), company size (SIZE), profitability (ROA), institutional ownership (INST), and managerial ownership (MOWN). Meanwhile, the dependent variable is the Debt to Equity Ratio or DER.Object of this research is manufacturing companies listed in Indonesia Stock Exchange in 2009 until 2013. The sample used in this study were 8 manufacturing company. The sampling method is done by using purposive sampling. Analysis of data using multiple linear regression analysis, which is preceded by the classical assumption, consisting of normality test, multicollinearity, autocorrelation, and heteroscedasticity test. Hypothesis testing is done by using the F test and t-test.The results of this study indicate that liquidity, sales growth, firm size, profitability, institutional ownership, and managerial ownership together influence the companyâ€™s debt policy. While, in partial, liquidity (CR),Â profitability (ROA), and managerial ownership (MOWN) significant negative effect on the DER. Variable institutional ownership (INST) did not significant negative effect on the DER. While, firm size (SIZE) and sales growth (SG) had no significant positive effect on the DER. The degree of determination (Adjusted R Square) is 0,457. This means that the independent variable (CR, ROA, SIZE, Sales Growth, INST, and MOWN) can explain the dependent variable (DER) by 45.7%. While, the remaining 54.3% is explained by other variables outside the model study.